THE LATEST TECHNOLOGIES OF PREPARING FUTURE SPECIALISTS FOR THE IMPLEMENTATION OF HEALTHCARE SAVING TECHNOLOGIES - І. Усатова; В. Ткаченко; А. Ведмедюк (Київський національний університет імені Тараса Шевченка, 2018)
In the article on the basis of scientific and pedagogical sources the ways of perfection of the system of professional education with the purpose of preparing the future specialist for the practical realization of the idea of health saving of the nation at all stages of educational activity are analyzed and solved. New approaches to the development of the content, forms and methods of professional training of specialists of the new formation, as well as introduction of the modern technologies in the educational process of higher educational institutions are studied. It is noted that the educational process should be transformed in the direction of individualization of educational interaction, learning, formation of creative thinking and increase of independent work of students. It is characterized that a specialist-innovator is the bearer of specific innovations, their creator, modifier, it has wide possibilities and has an unlimited field of activity, since in practice it is convinced of the efficiency of existing technologies and teaching methods and can correct them, carry out research work, develop new methods and technology. The focus of this activity is the innovative potential of a future specialist. The directions of introduction into the educational process of modern technologies are revealed, where the teacher becomes more and more the functions of a consultant, counselor, mentor, since in professional activity not only special subject knowledge is realized, but also modern knowledge in the field of pedagogy and psychology, acmeology, technology of education and upbringing. In the course of scientific research, the preconditions for creating a concept for forming the readiness of future specialists for the implementation of innovation as the basis for improving the educational process, the essence of which is the introduction of modern tools and methods into the traditional system of education, is outlined. the pedagogical conditions of effective use of health-saving technologies are formulated, essential characteristics and stages of training of future specialists in educational institutions are highlighted; substantiated the basic provisions, the observance of which provides the training of specialists of the new formation to the implementation of healthcare-saving technologies. It is emphasized that in the educational space of a higher educational institution it is necessary to create conditions that will promote the formation of the right attitude of health professionals to the health of the future as the main value of the person that will significantly stimulate their reflective activity and awareness of personal responsibility for the health of their pupils.

Розкрито шляхи удосконалення системи професійної освіти з метою підготовки майбутнього фахівця до практичного втілення ідеї здоров'язбереження нації на всіх етапах освітньої діяльності; з'ясовано нові підходи до розроблення змісту, форм і методів професійної підготовки фахівців нової формації; окреслено передумови створення концепції формування готовності майбутніх фахівців до здійснення інноваційної діяльності; сформульовано педагогічні умови ефективного використання здоров'язбережувальних технологій, висвітлено сутнісні характеристики та етапи підготовки майбутніх фахівців у закладах освіти; обґрунтовано основні положення, дотримання яких забезпечує підготовку фахівців нової формації до реалізації здоров'язбережувальних технологій.
НОВІТНІ ТЕХНОЛОГІЇ ПІДГОТОВКИ МАЙБУТНІХ ФАХІВЦІВ ДО РЕАЛІЗАЦІЇ ЗДОРОВ'ЯЗБЕРЕЖУВАЛЬНИХ ТЕХНОЛОГІЙ
Keywords: майбутній фахівець; новітні технології; здоров'язбережувальні технології; future specialist; the latest technologies; health-saving technologies